PENGENALAN DAN PEMBIASAAAN PERILAKU HIDUP SEHAT DAN BERSIH SEJAK DINI PADA SISWA SEKOLAH DASAR - Hukama, La Adhan; Razih, Muhammad; R, Rayhan Aneflin; R, Virjinea Hawani; Az-Zahra, Venezia; Fadlilah, Aldhaf; Larasati, Dinda Kania; Budi, Amanda Salsabila Audia; Mulya, Alzalisa Ridha; Lestari, Nabila Ayu; Aprilia, Nadia (ABDI WINA JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Sustainable Development Goals (SDGs) is a global and national agreement that aims to improve the welfare of society. One of the goals of the SDGs is a Healthy and Prosperous Life. In order to support the acceleration of the achievement of the SDGs, YARSI University organizes Real Work Lecture (KKN) activities with the theme "Cure The Earth". This activity aims to increase understanding in early childhood, especially elementary school students about the importance of maintaining environmental cleanliness and good waste management. The Community Development Practice method is used in this activity. The activity begins with the preparation stage which is carried out through observation to find out and identify the problems faced by partners. Second, the preparation of the work program, which was carried out based on the results of the analysis of the observation of the problems faced by partners and third, the implementation of counseling in the form of socialization of understanding of waste and its solutions. A total of 66 students in grade 5 and grade 6 of Cilincing 02 Pagi Elementary School, North Jakarta were involved in this activity. Before the activity was carried out, a pre-test was carried out to determine the level of students' knowledge of the material to be delivered and a post-test after the counseling activity was carried out which aimed to evaluate the end of the material taught. This activity went well because based on the results of the post test, there was an increase in understanding which was around 93.7% compared to before counseling which was only 49.3%.